2018
DOI: 10.1111/ejss.12680
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carbon pools and biological activities of a sandy loam soil under medium‐term conservation agriculture and diversified cropping systems

Abstract: Summary Conservation agriculture (CA) practices such as zero tillage (ZT) and permanent raised beds (PB) accelerate deposition of soil organic matter and augment associated biological properties of soil through enhanced inputs of organic carbon. However, the potential benefit of CA under intensive cereal‐based systems for key soil health indicators (such as carbon pools and biological activities) is only partially known. Therefore, we analysed the effect of three medium‐term tillage practices and four intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…Our findings are also consistent with the findings of Choudhary et al (2018a, b) and Parihar et al (2018) who also observed significantly higher TC under CA based practices.…”
Section: Soil Carbonsupporting
confidence: 93%
“…Our findings are also consistent with the findings of Choudhary et al (2018a, b) and Parihar et al (2018) who also observed significantly higher TC under CA based practices.…”
Section: Soil Carbonsupporting
confidence: 93%
“…Surface retention of crop residues under no-tillage system has been reported to greatly enhance the soil enzymatic activity, which was related to increased microbial biomass in the soil (Hok et al, 2018;Saikia et al, 2019). This has significance in RWCS, where alteration in moisture regimes during two seasons changed the pattern of microbial decomposition of C input into the soil triggered by enzymatic activity (Choudhary et al, 2018;Parihar et al, 2018). The TOC pools and enzymatic activity under different straw management regimes vary substantially depending on climate factors, soil types, and experimental conditions (Wang et al, 2015a;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Higher microbial activity in surface soil under CA‐based management also contributed to higher production of VLC in those scenarios (Choudhary, Datta, et al, 2018; Choudhary, Jat, et al, 2018). Parihar et al (2018) also reported higher VLC as MBC at surface soils under CA‐based management in Northwest India. All CA‐based managements resulted in higher SOC in comparison with CT.…”
Section: Discussionmentioning
confidence: 90%